E-053 Time is Brain: Standardizing Thrombectomy Metrics Leads to Faster Recanalization. (29th July 2016) - Frei, D; Loy, D; Bellon, R; Huddle, D
Abstract : Background: Acute stroke treatment has been proven to be most effective when performed immediately. The objective of our study was to describe the steps taken to improve time metrics for patients receiving intra-arterial therapy (IAT), and compare metrics before and after implementation of interventions. Hypothesis: Through streamlining the evaluation and treatment process of IAT, we predict our times between patient arrival, imaging, puncture and recanalization will be reduced. Methods: On June 1, 2013, we instituted a series of interventions in the interventional radiology suite to streamline care, including requiring the thrombolytic team to meet all transferred patients in the imaging room within 30 minutes of arrival, as well as introducing a wheeled stroke cart replete with a stroke tray containing all devices needed to perform a thrombectomy, standardizing the thrombectomy procedure, switching from general anesthesia to conscious sedation for all stroke patients, and no longer shaving the groin or using a foley catheter. We also added an additional biplane INR room, doubling our room capacity. We compared time metrics of patient arrival to imaging, imaging to puncture, and puncture to recanalization of acute ischemic stroke patients that received IAT before (1/1/12–5/31/13) and after (6/1/13–5/31/15) the interventions using univariate analysis. Results: Three hundred twenty-two patients received IAT during the study period. Nearly three quarters (73.3%) of the population was transferred from a referring facility. There were significantly less female patients in the post-intervention cohort (59.5% v 48.0%, p = 0.04); there were no significant differences in age, race, or initial NIHSS. We found statistically significant reductions in time between patient arrival to imaging (19.2 ± 9.6 v 13.6 ± 6.7, p < 0.000), imaging to puncture (57.9 ± 36.2 v 46.9 ± 40.5, p = 0.04), and puncture to recanalization (70.7 ± 47.3 v 53.1 ± 40.4, p = 0.004) after implementation of the interventions. Conclusions: Our initiatives allowed us to refine our process of care, resulting in a significant reduction of time between patient arrival and imaging, imaging to puncture, and puncture to recanalization. Disclosures: D. Frei: 1; C; Penumbra, Medtronic, Stryker, MicroVention, Sequent, Siemens, Codman. 2; C; Penumbra, Stryker, MicroVention, Codman, Siemens. 3; C; Penumbra, Stryker, MicroVention, Codman, Siemens. 4; C; Penumbra. D. Loy: None. R. Bellon: None. D. Huddle: None.